PCOS – The Importance of Diet, Physical Activity, and Other Non-Pharmacological Methods in Treatment - Turek, Monika; Wojciechowska, Klara; Jaroń, Aleksandra; Jastrzębska, Katarzyna; Wiklińska, Agata; Witkowska, Maria; Skotnicka, Joanna; Błaszczak, Karolina; Borkowski, Adrian; Sawicki, Mateusz (Quality in Sport, 2024)
Purpose of research: PCOS is one of the most common endocrine disorders. It is estimated to affect about 5-10% of women of reproductive age. This paper aims to highlight the challenges faced by those with PCOS and to demonstrate the importance of non-pharmacological methods in treating this condition. Methods: Databases such as PubMed, Medline, and ResearchGate were used. Basic results: PCOS is associated with menstrual irregularities and leads to reduced fertility, while commonly occurring hyperandrogenism causes unpleasant changes in appearance, such as hair loss, hirsutism, and acne. Women with PCOS also have an increased risk of developing type 2 diabetes, hypertension, and certain cancers. Conclusions: The first line of treatment for PCOS is lifestyle modification. Appropriate diet and weight loss aim to reduce inflammation, regulate the menstrual cycle, restore ovulation, and reduce the risk of cardiovascular disease and cancer. An important aspect is the intake of vitamins D and E, as well as inositol. Research shows that probiotics may also have a positive effect.